Four Arabic Legal Documents Belonging to ʿAmmār b. Salama b. ʿAbd al-Wārith - Younes, Khaled Mohamed (Der Islam, 2021)
This paper edits and studies four Arabic legal documents, written on two papyri, now housed in the Beinecke Rare Book and Manuscript Library at Yale University. The documents belong to a certain ʿAmmār b. Salama b. ʿAbd al-Wārith, a merchant from al-Bahnasā. Document 1 (P.CTYBR inv. 1720 verso) records a contract of sale of two inherited portions belonging to a Copt with double names, a Christian and a Muslim one. The contract touches on two significant socio-religious subjects: 1. name change after religious conversion, and 2. the loss of paternal filiation ( nasab ) of children born outside wedlock or in wedlock but their paternity was disavowed via the Islamic procedure of liʿān “oath of condemnation” or upon evidence of certain circumstances that prove impossibility of paternity. Documents 2.1, 2.2, and 2.3 (P.CTYBR inv. 1715 recto and verso) contains three debt acknowledgements recording payments in coin and in kind. All documents date to the year 297/909-910.